Buckling and delamination growth behaviour of delaminated composite panels subject to four-point bending. (15th March 2016) - Gong, Wenran; Chen, Jinlong; Patterson, Eann A.
Abstract: Buckling behaviour and delamination growth have been investigated in Carbon Fibre-Reinforced Plastic (CFRP) laminates with artificial and impact-induced delaminations when subject to four-point bending. The energy of the impact was such that the induced damage, observed using ultrasound, did not extend across the entire width of the laminates and was barely visible on the impacted face. Stereoscopic digital image correlation was used to measure the evolution of the deformation of the laminate during bending to structural failure; and the resulting full-field displacement maps and observations of failure modes from Scanning Electron Microscopy (SEM) were used to conclude that appropriately shaped and located artificial delaminations could be employed to represent damage-induced delaminations. This enabled the development of a non-linear Finite Element Analysis (FEA) incorporating a fibre/matrix constitutive model, a modified fibre/matrix failure criterion and a delamination growth criterion to examine the interaction between the buckling behaviour and delamination growth. The predictions of the surface displacements in bending were validated, with the aid of image decomposition, using the measured data fields for a crossply laminate. The model reliably predicted the load–displacement curve and the propagation of damage in laminates with a low level impact damage, which did not extend across the width of laminates, unlike in prior reported models.